Radon in homes and risk of lung cancer: collaborative analysis of individual data from 13 European case-control studies. Issue 7485 (21st December 2004) - Darby, S; Hill, D; Auvinen, A; Barros-Dios, J M; Baysson, H; Bochicchio, F; Deo, H; Falk, R; Forastiere, F; Hakama, M; Heid, I; Kreienbrock, L; et al.
Abstract: Objective To determine the risk of lung cancer associated with exposure at home to the radioactive disintegration products of naturally occurring radon gas Design Collaborative analysis of individual data from 13 case-control studies of residential radon and lung cancer. Setting Nine European countries. Subjects 7148 cases of lung cancer and 14 208 controls. Main outcome measures Relative risks of lung cancer and radon gas concentrations in homes inhabited during the previous 5-34 years measured in becquerels (radon disintegrations per second) per cubic metre (Bq/m 3 ) of household air. Results The mean measured radon concentration in homes of people in the control group was 97 Bq/m 3, with 11% measuring > 200 and 4% measuring > 400 Bq/m 3 . For cases of lung cancer the mean concentration was 104 Bq/m 3 . The risk of lung cancer increased by 8.4% (95% confidence interval 3.0% to 15.8%) per 100 Bq/m 3 increase in measured radon (P = 0.0007). This corresponds to an increase of 16% (5% to 31%) per 100 Bq/m 3 increase in usual radon—that is, after correction for the dilution caused by random uncertainties in measuring radon concentrations. The dose-response relation seemed to be linear with no threshold and remained significant (P = 0.04) in analyses limited to individuals from homes with measured radon < 200 Bq/m 3 . The proportionate excess risk did not differ significantly with study, age, sex, or smoking. In the absence of other causes of death, the absolute risks of lung cancer by age 75 years at usual radon concentrations of 0, 100, and 400 Bq/m 3 would be about 0.4%, 0.5%, and 0.7%, respectively, for lifelong non-smokers, and about 25 times greater (10%, 12%, and 16%) for cigarette smokers. Conclusions Collectively, though not separately, these studies show appreciable hazards from residential radon, particularly for smokers and recent ex-smokers, and indicate that it is responsible for about 2% of all deaths from cancer in Europe.